Adam Mikołaj Sieniawski and Diplomatical Activity of the Polish-Lithuanian Commonwealth after the Restoration of King Augustus II in the Years 1709–1713: Remarks Concerning the Expeditions of Diplomats Sent by the Hetman and Polish-Lithuanian Commonwealth to the Ottoman Empire and the Crimean Khanate - Link-Lenczowski, Andrzej K. (Verba volant, scripta manent: Księga jubileuszowa dedykowana Profesorowi Zbigniewowi Anusikowi w sześćdziesiątą piątą rocznicę urodzin, 2022)
The author examines the diplomacy of the Polish-Lithuanian Commonwealth as a system that subordinates states activity in the international arena to several centres (the Diet, hetmans, magnates). The diplomats sent in the name of the King and Polish-Lithuanian Commonwealth were sometimes the representatives of the Crown, the King, and sometimes only of the hetmans. The difficulty lies in the real dependence on the individual principals.